2010
DOI: 10.1021/jp911908c
|View full text |Cite
|
Sign up to set email alerts
|

Preferential CO Oxidation in a H2-Rich Stream on Pt−ReOx/SiO2: Catalyst Structure and Reaction Mechanism

Abstract: Modification of Pt/SiO 2 with ReO x species enhanced the catalytic activity of the CO oxidation with O 2 in the presence of H 2 . The amount of Re modifier on Pt-ReO x /SiO 2 was optimized to be Re/Pt ) 0.5 on the molar basis. The promoting effect of Re species appeared after the reduction above 673 K. Characterization of the reduced Pt-ReO x /SiO 2 catalyst by means of EXAFS, XANES, temperature-programmed reduction, and CO adsorption measurements suggested the formation of the ReO x clusters on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 62 publications
9
64
0
Order By: Relevance
“…Only for the Ru 50 -Re 50 catalyst, the O 2 adsorption at RT is 16% lower than that of the Ru catalyst which suggests a smaller extent of the subsurface ruthenium oxidation probably because of the larger covering of the RuRe nanoparticles with ReO x species. Literature data also show that in the Pt-Re/SiO 2 [27], Rh-Re/SiO 2 [28] and Ir-Re/SiO 2 [29] catalysts Pt, Rh or Ir metal surface was partially covered by the two-dimensional Re oxide clusters. At adsorption temperature of 150 • C, the complete oxidation of the metal phase in the Ru 90 -Re 10 and Ru 75 -Re 25 catalysts occurs, while in the Ru 50 -Re 50 sample full oxidation is not attained even at 250 • C. Since in this catalyst some fraction of Re is segregated [20], thus at 250 • C spreading of the rhenium oxide species from the Re metal particles both on the Ru phase and the ␥-alumina surface occurs causing additional covering of the Ru surface with ReO x species, thus hindering O 2 adsorption.…”
Section: Catalystmentioning
confidence: 86%
“…Only for the Ru 50 -Re 50 catalyst, the O 2 adsorption at RT is 16% lower than that of the Ru catalyst which suggests a smaller extent of the subsurface ruthenium oxidation probably because of the larger covering of the RuRe nanoparticles with ReO x species. Literature data also show that in the Pt-Re/SiO 2 [27], Rh-Re/SiO 2 [28] and Ir-Re/SiO 2 [29] catalysts Pt, Rh or Ir metal surface was partially covered by the two-dimensional Re oxide clusters. At adsorption temperature of 150 • C, the complete oxidation of the metal phase in the Ru 90 -Re 10 and Ru 75 -Re 25 catalysts occurs, while in the Ru 50 -Re 50 sample full oxidation is not attained even at 250 • C. Since in this catalyst some fraction of Re is segregated [20], thus at 250 • C spreading of the rhenium oxide species from the Re metal particles both on the Ru phase and the ␥-alumina surface occurs causing additional covering of the Ru surface with ReO x species, thus hindering O 2 adsorption.…”
Section: Catalystmentioning
confidence: 86%
“…The formation of ReOx clusters on the surface of metal particles has also been reported in other metal-Re bimetallic systems such as Pt-ReOx. [29,30] Catalytic Performance in the Hydrogenolysis of Various Substrates Using Ir-ReO x /SiO 2 Catalyst in Water and Alkane Solvents Activity tests as well as reduction of the catalysts were performed in a 190 mL stainless steel autoclave with an inserted glass vessel. The catalyst (25-100 mg), a spinner and the reaction solvent (n-heptane or water; typically 10 mL) were placed into the autoclave and heated at 473 K under 8 MPa H2 for 1 h for the reduction pretreatment.…”
Section: Preparation and Structure Of Ir-reo X /Sio 2 Catalystsmentioning
confidence: 99%
“…The Pd À Re bond was also observed, suggesting that a part of the Re species are attached on the Pd particles like it is the case for ReO x -modified Ir, Pt, and Rh metal catalysts. [5,11,36] The reaction mechanism of the hydrodeoxygenation of 1,4-AHERY on ReO x -Pd/CeO 2 is discussed here. Toste et al have reported CH 3 ReO 3 -catalyzed deoxydehydration of 1,4-AHERY to 2,5-dihydrofuran.…”
mentioning
confidence: 99%